The Role of Brand Attitude to Mediate Electronic Word of Mouth on Purchase Intention - Bundu, Velicia N; Zakaria, Zakaria; Labo, Irwan Adam (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to investigate the role of Brand Attitude as a mediator in the relationship between Electronic Word of Mouth (eWOM) and Purchase Intention. Research Design and Methodology: His research employs a quantitative survey approach. Data were collected from 171 respondents who were guests at Suni Garden Lake Hotel & Resort Sentani. The validity and reliability of the research instruments were tested, and analysis was conducted using Structural Equation Modeling (SEM) to examine the relationships between variables. Findings and Discussion: The main findings indicate that eWOM positively and significantly affects Brand Attitude and purchase Intention. The regression results show that Brand Attitude mediates the relationship between eWOM and Purchase Intention, thus strengthening the impact of eWOM on consumer purchase decisions. Implication: The implications of this study highlight the importance of effectively managing eWOM to enhance Brand Attitude and Purchase Intention. Marketers can leverage positive reviews and constructive interactions on social media to strengthen Brand Attitude. This study also opens opportunities for further research to explore how specific elements of eWOM influence Brand Attitude and Purchase Intention across different demographic segments and cultural contexts.